Debt to Equity Ratio (DER), Earning Per Share (EPS) Analysis of Company Value at PT Indosat, Tbk - Desi Ratnasari; Puji Muniarty (Yayasan Ilomata, 2020)
This study aims to analyze the effect of independent variables on the dependent variable. The independent variables are Debt to Equity Ratio (DER) and Earning Per Share (EPS) while the dependent variable is the Company Value at PT Indosat, Tbk for the period 2004-2018. The sample in this study over the past 15 years, namely from the period 2004-2018. The data used in this study is to use the company's financial statement data published on the Indonesia Stock Exchange (IDX) website and the company's official website. The data used are secondary data and the method used is regression analysis that is Time series data with the help of SPSS version 20.0 to get a picture of the relationship between one variable and another. The results showed that DER has no effect and no significant effect on firm value, EPS has no effect and no significant effect on firm value, DER and EPS simultaneously have no effect and no significant effect on firm value. The influence of DER and EPS on Company Value is 36.4% while the remaining 63.6% is influenced by other factors not included in the research model.